Characterization of Plastic Clay and Prophyllite Used as Adsorbents for the Removal of Pollutants - Rai, Kalpna; Jaiswal, Mona; Maheshwari, A. (Asian Journal of Chemistry, 2010)
Studies were made in search of non-conventional cheap adsorbents to use them for waste water treatment. Clay minerals, namely plastic clay and prophyllite, were characterised with IR, XRD and standard methods of chemical analysis. These have been tried for the removal of phenol, o-nitrophenol, p-nitrophenol. o-cresol, m-cresol, p-cresol, oxalate, Cr(VI), PO3–4 through batch adsorption and the results confirmed these to be good adsorbents.